Serpin-Derived Peptides Are Antiangiogenic and Suppress Breast Tumor Xenograft Growth - Koskimaki, Jacob E (Neoplasia Press Inc., 2012)
Angiogenesis is the formation of neovasculature from preexisting microvessels. Several endogenous proteins regulate the balance of vessel formation and regression in the body including pigment epithelium-derived factor (PEDF), which has been shown to be antiangiogenic and to suppress tumor growth. Using sequence homology and bioinformatics, we previously identified several peptide sequences homologous to an active region of PEDF existing in multiple proteins in the human proteome. These short 11-mer peptides are found in a DEAH box helicase protein, CKIP-1 and caspase 10, and show similar activity in altering endothelial cell adhesion, migration and inducing apoptosis.We tested the peptide derived from DEAH box helicase protein in a triple-negative MDA-MB-231 breast orthotopic xenograft model in severe combined immunodeficient mice and show significant tumor suppression.